The Legal Implications of Covid-19 on Revenue Generation in a Depressed Economy: The Nigerian Experience (Law Research Review Quarterly, 2020)
The world economy is driven by trade and commerce, through the movement of goods and services from one location to the other. Trade and commerce can only be achieved by a healthy, productive class or populace to consume the goods produce or enjoy the service. Consequently, the government can generate the desired revenue to provide its citizens with basic infrastructure and also guarantee development. Once the health index of the production class and/ or the general populace is at risk, the chain of production and consumption will be disrupted. There will be a negative impact on the economy, thus affecting the incomes and the general dynamics of businesses. This disruption will put a clog on the expected revenue to be generated and hamper or cripple economic development. This will be worst when such disruption is on a national or global scale that can be considered as a pandemic like SARS or COVID-19. Disruption on a monumental scale like the ongoing disruption caused by COVID-19 has restricted the movement of human beings, goods, and services across the globe. The thrust of this research is to examine the relationship between public health and the economy as a catalyst for revenue generation, with development as a by-product. Doctrinal research was used and based on findings, the paper recommends amongst others, the use of e-governance and digital economy in our daily lives and activities particularly in our economic activities and revenue generations.